Burkitt lymphoma risk in U.S. solid organ transplant recipients. Issue 4 (6th February 2013) - Mbulaiteye, Sam M.; Clarke, Christina A.; Morton, Lindsay M.; Gibson, Todd M.; Pawlish, Karen; Weisenburger, Dennis D.; Lynch, Charles F.; Goodman, Marc T.; Engels, Eric A.
<x xml:space="preserve">Abstract</x> Case reports of Burkitt lymphoma (BL) in transplant recipients suggest that the risk is markedly elevated. Therefore, we investigated the incidence of BL in 203, 557 solid organ recipients in the U.S. Transplant Cancer Match Study (1987–2009) and compared it with the general population using standardized incidence ratios. We also assessed associations with demographic and clinical characteristics, and treatments used to induce therapeutic immunosuppression. BL incidence was 10.8 per 100, 000 person‐years, representing 23‐fold (95% confidence interval (CI) 19–28) greater risk than in the general population, and it peaked 3–8 years after the time of transplantation. In adjusted analyses, BL incidence was higher in recipients transplanted when <18 vs. ≥35 years (incidence rate ratio [IRR] 3.49, 95% CI 2.08–5.68) and in those transplanted with a liver (IRR 2.91, 95% CI 1.68–5.09) or heart (IRR 2.39, 95% CI 1.30–4.31) compared with kidney. BL incidence was lower in females than males (IRR 0.45, 95% CI 0.28–0.71), in blacks than whites (IRR 0.33, 95% CI 0.12–0.74), in those with a baseline Epstein‐Barr virus (EBV)‐seropositive versus EBV‐seronegative status (IRR 0.34, 95% CI 0.13–0.93), and in those treated with azathioprine (IRR 0.56, 95% CI 0.34–0.89) or corticosteroids (IRR 0.48, 95% CI 0.29–0.82). Tumors were EBV‐positive in 69% of 32 cases with results. EBV positivity was 90% in those aged <18 years and 59% in those aged 18+ years. In conclusion, BL risk is markedly elevated in transplant recipients, and it is associated with certain demographic and clinical features. EBV was positive in most but not all BL cases with results. Am. J. Hematol. 88:245–250, 2013. © 2012 Wiley Periodicals, Inc.